(untitled) (Research, Society and Development, 2025)
Objective: To evaluate the effectiveness of interventions aimed at Brazilian children and adolescents in situations of social vulnerability on outcomes of child development. Methods: A systematic review conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) and a protocol registered with the International Prospective Register of Systematic Reviews - PROSPERO (No. CRD42023442457), conducted between 2022 and 2023, across databases including Medline, PubMed, Scielo, Embase, Cochrane, Scopus, CINAHL, Web of Science, PEDro, and Lilacs. The Cochrane scale was used to assess risk of bias, and the quality of evidence was evaluated using the Grading of Recommendations Assessment, Development, and Evaluation. Results: Ten studies were included, encompassing 7,134 children and adolescents in situations of social vulnerability. While not all studies showed significant changes, all identified some positive change in favor of the intervention. Outcomes such as mortality, infections, and diarrhea had the best results, with these indicators showing sensitivity to change with basic interventions like vaccination and surveillance. A lack of scientific production regarding programs and actions for the study population was also noted. Conclusion: It is essential to expand scientific research on programs and actions targeting this population to develop more comprehensive and effective strategies that address the persistent challenges in these communities.